Inhibition mechanism of naphthylphenylamine derivatives acting on the CDC25B dual phosphatase and analysis of the molecular processes involved in the high cytotoxicity exerted by one selected derivative in melanoma cells - Federica Aliotta; Rosarita Nasso; Rosario Rullo; Alessandro Arcucci; Angelica Avagliano; Martina Simonetti; Gennaro Sanità; Mariorosario Masullo; Antonio Lavecchia; Maria Rosaria Ruocco; Emmanuele De Vendittis (Taylor & Francis Group, 2020)
The dual phosphatases CDC25 are involved in cell cycle regulation and overexpressed in many tumours, including melanoma. CDC25 is a promising target for discovering anticancer drugs, and several studies focussed on characterisation of quinonoid CDC25 inhibitors, frequently causing undesired side toxic effects. Previous work described an optimisation of the inhibition properties by naphthylphenylamine (NPA) derivatives of NSC28620, a nonquinonoid CDC25 inhibitor. Now, the CDC25B•inhibitor interaction was investigated through fluorescence studies, shedding light on the different inhibition mechanism exerted by NPA derivatives. Among the molecular processes, mediating the specific and high cytotoxicity of one NPA derivative in melanoma cells, we observed decrease of phosphoAkt, increase of p53, reduction of CDC25 forms, cytochrome c cytosolic translocation and increase of caspase activity, that lead to the activation of an apoptotic programme. A basic knowledge on CDC25 inhibitors is relevant for discovering potent bioactive molecules, to be used as anticancer agents against the highly aggressive melanoma.